2022
DOI: 10.1101/2022.03.06.483175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensory Tetanization to Induce LTP-Like Plasticity: A Review and Reassessment of the Approach

Abstract: Background: Great interest has been given to developing non-invasive approaches for studying cortical plasticity in humans. High frequency presentation of auditory and visual stimuli, or sensory tetanization, can induce LTP-like changes in cortical activity. However, contrasting effects across studies suggest that sensory tetanization may be unreliable. Method: We used sensory tetanization to try to induce auditory and visual LTP-like plasticity in younger and older adults. We measured auditory-evoked amplitud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
(266 reference statements)
0
3
0
Order By: Relevance
“…Additionally, it is important to note that there is large cross‐study variability in the sensory LTP literature. Some have questioned if sensory LTP is even a valid construct (Dias et al, 2022), and the largest studies have shown modest and inconsistent effects across hundreds of participants (Valstad et al, 2020). Our finding of response stability with repeated stimulus presentation further emphasizes that sensory LTP may not be a robust phenomenon and/or may only occur under a narrow range of stimulus parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is important to note that there is large cross‐study variability in the sensory LTP literature. Some have questioned if sensory LTP is even a valid construct (Dias et al, 2022), and the largest studies have shown modest and inconsistent effects across hundreds of participants (Valstad et al, 2020). Our finding of response stability with repeated stimulus presentation further emphasizes that sensory LTP may not be a robust phenomenon and/or may only occur under a narrow range of stimulus parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Although initial demonstrations of human sensory LTP were encouraging, and at least two regimes of sensory stimulation have been shown to induce LTP‐like effects (9–10 Hz flicker stimuli, and 2 Hz contrast‐reversing stimuli; Sanders et al, 2018), recent large studies of sensory LTP have shown inconsistent and highly variable neuroplastic effects following the use of sensory LTP protocols (Valstad et al, 2020), leading some to question if sensory LTP is a valid construct (Dias et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is important to note along these lines that there is large variability in the sensory LTP literature. Some have questioned if sensory LTP is even a valid construct (Dias et al, 2022), and the largest studies have shown modest if any consistent effects across hundreds of participants (Valstad et al, 2020). Our finding of response stability with repeated stimulus presentation provides further support for VEP stability, but a more thorough investigation of stimulus parameters is needed to determine in what regime ssVEP stimuli do or do not generate neuroplastic effects.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time results are rather inconsistent, probably related to different experimental designs across studies [4-6, 12, 24-27]. Moreover, the recent meta-analysis [28] revealed that the overall effect of tetanization across ERP studies is not significant. However this meta-analysis pointed to the relatively few studies on auditory tetanization that might be of importance due to potential link to speech development.…”
Section: Introductionmentioning
confidence: 99%